Minimal and Maximal Feebly Open Sets - Shakir, Qays (Iraqi Journal of Science, 2024)
In this paper we introduced many new concepts all of these concepts completelydepended on the concept of feebly open set. The main concepts which introduced inthis paper are minimal f-open and maximal f-open sets. Also new types oftopological spaces introduced which called Tf min and Tf max spaces. Besides,we present a package of maps called: minimal f-continuous, maximal f-continuous,f-irresolute minimal, f-irresolute maximal, minimal f-irresolute and maximal firresolute.Additionally we investigated some fundamental properties of the conceptswhich presented in this paper.